Research on parameter optimisation of tracked vehicle transmission system based on genetic algorithm. (14th January 2021) - Wei, Lingjun; Liu, Haiou; Chen, Huiyan; Xu, Yi; Zhao, Ziye
Based on the theoretical analysis of optimisation parameters and evaluation objectives, this paper applies computer simulation technology and objective optimisation theory to the parameter optimisation design of tracked vehicle power transmission system by using the basic idea of genetic algorithm. The transmission ratio and main deceleration ratio of transmission are taken as design variables to ensure trafficability, and fuel consumption is taken as a measure of tracked vehicle. The objective function of fuel economy is to establish the mathematical model of target optimisation of tracked vehicle transmission system with acceleration time and climbing slope as constraints. Compared with the original scheme, the traction characteristics and fuel economy of the optimised scheme are greatly improved. It is proved that the genetic algorithm can greatly improve the optimal design method of transmission system.